1973
DOI: 10.1111/j.1745-6606.1973.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Reaction to Nutritional Labels on Food Products

Abstract: In order to design the most useful instruments of consumer protection, it is necessary to understand how consumers perceive and use such instruments. Often, basic consumer rights are considered more extensively in the design of consumer protection policies than basic patterns of consumer behavior and motivation. We are more likely to make information on labels complete as viewed by the expert than useful in the normal behavior of the consumer. This study is devoted to discovering how consumers perceive nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…But, then as now, labeling requirements are slow to take effect. In 1973, nearly 100% of over 2000 people interviewed in the US were in favor of a nutrition label on food products [84]. Yet, the US Nutrition Labeling and Education Act did not pass until 1990 and was not implemented until 1994.…”
Section: Discussionmentioning
confidence: 98%
“…But, then as now, labeling requirements are slow to take effect. In 1973, nearly 100% of over 2000 people interviewed in the US were in favor of a nutrition label on food products [84]. Yet, the US Nutrition Labeling and Education Act did not pass until 1990 and was not implemented until 1994.…”
Section: Discussionmentioning
confidence: 98%
“…One explanation of the inadequate utilization of nutrition information could be that most consumers do not understand such information. Lenahan, et a1 report that only 16 percent of 2,150 consumers they surveyed in 1972 claimed to understand nutrition information [24]. Similarly, Jacoby, et a1 found that consumers intercepted in a shopping mall scored low on a test of nutrition comprehension [20].…”
Section: Nutritional Information and Dietary Habitsmentioning
confidence: 99%
“…Researchers have studied perishable groceries in terms of pricing (Rajan, Steinberg, and Steinberg ), inventory (Hariga ), ordering and restocking policies (Fujiwara, Soewandi, and Sedarage ), store choice (Krider and Weinberg ), food labels (Jahn, Schramm, and Spiller ; Lenahan et al ; Mackey and Metz ; Wansink and Chandon ), and health and safety (Dodd and Morse ; Michaelidou and Hassan ; Rydén, Sydner, and Hagfors ). Although these studies provide insights into the various factors affecting the management and purchase of perishable grocery products, a void still exists in terms of understanding consumers' motivation to search for expiration dates while shopping for and before consumption of perishable products.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%